Intercultural Pronunciation Variations and Adjustment Strategies among EFL Students from Java, Nusa Tenggara, and Papua - Suciati; Muhammad Misbahul Munir; Wafi, Muhammad Khoirul; Alzahriya, Asyana Isna Ummu (Langkawi: Journal of The Association for Arabic and English, 2025)
This study examines the pronunciation variations and adaptations of cross-cultural students from Java, Nusa Tenggara, and Papua in learning English as a foreign language. The study aims to  analyze  what the differences of pronunciation variations among the three groups of students are and explore how they adapt their native language pronunciation to standard English pronunciation. This study used a qualitative descriptive design with data collection through audio recordings, observations, and semi-structured interviews with students taking English subject. The variation analysis focused on segmental and suprasegmental aspects, including word stress, intonation, and speech rhythm. The results show clear pronunciation variations: Javanese students tend to place word stress stably, Nusa Tenggara students display dynamic intonation influenced by their regional phonological patterns, while Papuan students exhibit a syllable-timed rhythm with a tendency to add vowels at the end of words. Despite their differences, all groups were able to gradually adapt to standard English pronunciation through conscious imitation, listening practice, and increased prosodic awareness. These findings support the theory of interlanguage phonology (Selinker) and the principle of intelligibility (Jenkins) which states that successful pronunciation learning is determined more by clarity of communication than by similarity to a native speaker's accent. The implications of this research emphasize the need for pronunciation instruction that integrates prosodic practice and cross-cultural awareness to improve intelligibility while maintaining students' linguistic identity.